Blood lactate and stroke parameters during front crawl in elite swimmers with disability - Bentley, D. J.; Phillips, G.; McNaughton, L. R.; Batterham, A. M. (The Journal of Strength and Conditioning Research, 2002)
The purpose of this investigation was to compare the blood lactate concentration ([La]), stroke distance (Ds), and swim index (SI) during an incremental swim test (IST) in elite swimmers who had a loss in mobility (LM) (n = 6) or who had full mobility (FM) (n = 5) of the lower limbs. The IST consisted of 5 repeats of either 100 or 200 m front crawl depending upon the ability level of the swimmer. The [La] and heart rate measured during the IST showed no significant differences (p > 0.05). However, velocity (Vs) and Ds were all significantly lower (p < 0.01) during the IST. SI was significantly (p < 0.01) lower during repeats 1 to 3 and 5, but not repeat 4. These data indicate that the [La] response to incremental exercise is similar during incremental front crawl activity in swimmers suffering from loss of lower limb mobility. However, a critical Vs is reached in LM swimmers where swimming efficiency is optimal compared with FM swimmers.